European Association for Neuro-Oncology (EANO) guidelines for palliative care in adults with glioma. Issue 6 (June 2017) - Pace, Andrea; Dirven, Linda; Koekkoek, Johan A F; Golla, Heidrun; Fleming, Jane; Rudà, Roberta; Marosi, Christine; Rhun, Emilie Le; Grant, Robin; Oliver, Kathy; Oberg, Ingela; Bulbeck, Helen J; et al.
Summary: Patients with glioma present with complex palliative care needs throughout their disease trajectory. The life-limiting nature of gliomas and the presence of specific symptoms related to neurological deterioration necessitate an appropriate and early palliative care approach. The multidisciplinary palliative care task force of the European Association of Neuro-Oncology did a systematic review of the available scientific literature to formulate the best possible evidence-based recommendations for the palliative care of adult patients with glioma, with the aim to reduce symptom burden and improve the quality of life of patients and their caregivers, particularly in the end-of-life phase. When recommendations could not be made because of the scarcity of evidence, the task force either used evidence from studies of patients with systemic cancer or formulated expert opinion. Areas of palliative care that currently lack evidence and thus deserve attention for further research are fatigue, disorders of behaviour and mood, interventions for the needs of caregivers, and timing of advance care planning.